Silicon Nanowires/Pt for Enhanced Photo-Electrochemical Water Splitting Properties - Xu, Tianhao; Lu, Zhiyi; Li, Yingjie; Xu, Haijun; Wang, Liren; Sun, Xiaoming (Asian Journal of Chemistry, 2015)
Incorporation of co-catalysts onto silicon-based nanomaterials has been diligently pursued as photocatalysts for water splitting. Here we employ a metal-assisted chemical etching method to fabricate different types (p type and n type) of silicon nanowire arrays (Si NWs), followed by the Pt deposition outside. The resulting Si NWs/Pt exhibits much enhanced photo-electrochemical properties, with higher photocurrent density and lower onset potential relative to the pristine silicon nanowire arrays and planar silicon due to the high surface roughness of silicon nanowire arrays and the addition of Pt catalyst. We have also demonstrated that different types of Si NWs/Pt show different enhancement effects for oxygen evolution reaction and hydrogen evolution reaction under illumination. This study demonstrates an excellent photo-electrochemical catalyst for water splitting and provides a valuable guidance for choosing the right type of silicon in terms of the target chemical reaction.